Determination of ?-Aminopropyltriethoxysilane and Amino Group on Nanosilica-Doped ?-Aminopropyltriethoxysilane Composites Using Perchloric Acid - Li, Deliang; Qu, Jianying; Chang, Zhixian; Zhang, Zhijun (Asian Journal of Chemistry, 2010)
The prepared nanosilica-doped γ-aminopropyltriethoxysilane (APS) composites (APS-SiO2) were characterized by means of transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), thermogravimetric analysis (TGA) and Fourier transform infrared spectroscopy (FT-IR). Then a method to determine content of APS and amino in APS-SiO2 through titration with the perchloric acid-glacial acetic acid standard solution in non-aqueous solution was established. Influence of solvent, amount of acetic anhydride, the dispersant and its amount on results were discussed in detail and the end point was indicated by a potentiometric titration method. For the titration of APS-SiO2, the influence of nanoparticles' concentration on results was also discussed. Because of the addition of 2-ethylhexanol, the dispersibility of sample was improved, at the same time, the freezing point of the titration system was decreased. Therefore, the stability of the system was improved and the applied field of this method was developed. It was found that this method is simple in terms of operation and can be readily used to determine the purity of APS and amino on APS-SiO2 with good accuracy and reproducibility.